CompTIA PenTest+ study guide exam PT0-002 - Chapple, Mike; Seidl, David (John Wiley & Sons, Inc., 2021)
Prepare for success on the new PenTest+ certification exam and an exciting career in penetration testing In the revamped Second Edition of CompTIA PenTest+ Study Guide: Exam PT0-002, veteran information security experts Dr. Mike Chapple and David Seidl deliver a comprehensive roadmap to the foundational and advanced skills every pentester (penetration tester) needs to secure their CompTIA PenTest+ certification, ace their next interview, and succeed in an exciting new career in a growing field. You'll learn to perform security assessments of traditional servers, desktop and mobile operating systems, cloud installations, Internet-of-Things devices, and industrial or embedded systems. You'll plan and scope a penetration testing engagement including vulnerability scanning, understand legal and regulatory compliance requirements, analyze test results, and produce a written report with remediation techniques. This book will: Prepare you for success on the newly introduced CompTIA PenTest+ PT0-002 Exam Multiply your career opportunities with a certification that complies with ISO 17024 standards and meets Department of Defense Directive 8140/8570.01-M requirements Allow access to the Sybex online learning center, with chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms Perfect for anyone preparing for the updated CompTIA PenTest+ certification exam, CompTIA PenTest+ Study Guide: Exam PT0-002 is also a must-read resource for aspiring penetration testers and IT security professionals seeking to expand and improve their skillset.